Revolutionizing Ophthalmology: The Empowering Role of Artificial Intelligence: Doi: 10.36351/pjo.v40i2.1807 - Zahid Kamal Siddiqui; Muhammad Moin; Hafiza Sadia Imtiaz (Pakistan Journal of Ophthalmology, 2024)
Artificial Intelligence holds immense importance in today’s world and has the potential to alter our future in various domains. The importance of AI lies in its ability to automate tasks, enhance decision-making, personalize experiences, solve complex problems, and drive innovation. Choosing not to adopt AI may result in inefficiency, missed opportunities, limited innovation, reduced insights, and higher operational costs. It won’t be long before the lives of those who benefit from AI and those who don’t will diverge significantly. According to Stephen Hawking.